(untitled) (Journal of Organizational Psychology, 2017)
This paper explores the differences in employees’ knowledge sharing behaviors when interacting with targets from different hierarchal positions in an organization. Eleven mid-level employees working in small and medium-sized enterprises in Hong Kong were interviewed for the exploratory purpose. The interview corpus, which consisted of 30,000 words, showed how and why mid-level employees differ in their knowledge sharing with different target audiences: their superiors, peers and subordinates. Theoretically, the findings advance our understanding of employees’ decisions on knowledge sharing behavior; and, in practical terms, the findings inform managers about how employees’ behavior is affected by hierarchal relationships in the workplace.